2021
DOI: 10.1097/qai.0000000000002639
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Successful Enrollment in a Proof-of-Concept HIV Prevention Trial of VRC01, a Broadly Neutralizing HIV-1 Monoclonal Antibody

Abstract: the HVTN 704/HPTN 085 study group Background: The Antibody-Mediated Prevention trials (HVTN 704/ HPTN 085 and HVTN 703/HPTN 081) are the first efficacy trials to evaluate whether VRC01, a broadly neutralizing monoclonal antibody targeting the CD4-binding site of the HIV envelope protein, prevents sexual transmission of HIV-1. HVTN 704/HPTN 085 enrolled 2701 cisgender men and transgender (TG) individuals who have sex with men at 26 sites in Brazil, Peru, Switzerland, and the United States.Methods: Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…The NIAID-funded HIV Vaccine Trials Network (HVTN) and HIV Prevention Trials Network (HPTN) therefore collaborated on the design and conduct of the two Antibody Mediated Prevention (AMP) trials, HVTN 704/HPTN 085 (NCT02716675) and HVTN 703/HPTN 081 (NCT02568215) ( 107 ). HVTN 704/HPTN 085 enrolled 2,699 cisgender men and transgender (TG) people who have sex with men in Brazil, Peru, Switzerland, and the US ( 108 ) while HVTN 703/HPTN 081 enrolled 1,924 cisgender women in Botswana, Kenya, Malawi, Mozambique, South Africa, Tanzania, and Zimbabwe ( 109 ).…”
Section: Clinical Evaluation Of Bnabsmentioning
confidence: 99%
“…The NIAID-funded HIV Vaccine Trials Network (HVTN) and HIV Prevention Trials Network (HPTN) therefore collaborated on the design and conduct of the two Antibody Mediated Prevention (AMP) trials, HVTN 704/HPTN 085 (NCT02716675) and HVTN 703/HPTN 081 (NCT02568215) ( 107 ). HVTN 704/HPTN 085 enrolled 2,699 cisgender men and transgender (TG) people who have sex with men in Brazil, Peru, Switzerland, and the US ( 108 ) while HVTN 703/HPTN 081 enrolled 1,924 cisgender women in Botswana, Kenya, Malawi, Mozambique, South Africa, Tanzania, and Zimbabwe ( 109 ).…”
Section: Clinical Evaluation Of Bnabsmentioning
confidence: 99%
“…Recent studies have shown that passively infused broadly neutralizing monoclonal antibodies (bnAbs) exhibit favorable safety profiles and are promising strategies for therapy and prevention of HIV-1 (5)(6)(7). The Antibody Mediated Prevention (AMP) studies substantiated the concept that a bnAb can prevent HIV acquisition (5,(8)(9)(10). In addition to prevention of HIV-1 infection, bnAbs are being investigated as an approach to achieve viral control without the use of antiretroviral therapy (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the first efficacy trials of an antibody for HIV prevention tested in Africa and the Americas have recently been published (14)(15)(16)(17). These two Antibody-Mediated Prevention (AMP www.ampstudy.org.za) trials showed that VRC01 had 75% prevention efficacy in high-risk men and women if the infecting virus was sensitive to the antibody at <1mg/ml (IC 80 ).…”
Section: Introductionmentioning
confidence: 99%